2020
DOI: 10.1021/acschemneuro.0c00332
|View full text |Cite
|
Sign up to set email alerts
|

Classics in Chemical Neuroscience: Pramipexole

Abstract: Pramipexole was first manufactured by Pharmacia and Upjohn in July 1997 under the United States brand names of Mirapex and Mirapex ER. Pramipexole is classified as a nonergoline aminobenzothiazole compound that selectively agonizes the dopamine D2-like receptor subfamily, which includes the D2, D3, and D4 receptor subtypes. Pramipexole is a unique compound in its therapeutic potential because it has D3-preferring properties. The D3 receptor target has implications in both motor and psychiatric symptoms of Park… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…They should be administered 2 to 3 hours before bedtime to relieve RLS in PD [ 73 ] but DA agonists also have many side effects. For example, high doses of dopaminergic agonists can result in visual hallucinations that are dose-related [ 74 ]. Pramipexole has a higher risk of ICD compared to other DA agonists due to its affinity for the D3 receptor [ 74 ].…”
Section: Sleep Disorders and Pharmacological Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…They should be administered 2 to 3 hours before bedtime to relieve RLS in PD [ 73 ] but DA agonists also have many side effects. For example, high doses of dopaminergic agonists can result in visual hallucinations that are dose-related [ 74 ]. Pramipexole has a higher risk of ICD compared to other DA agonists due to its affinity for the D3 receptor [ 74 ].…”
Section: Sleep Disorders and Pharmacological Treatmentsmentioning
confidence: 99%
“…For example, high doses of dopaminergic agonists can result in visual hallucinations that are dose-related [ 74 ]. Pramipexole has a higher risk of ICD compared to other DA agonists due to its affinity for the D3 receptor [ 74 ]. In PD patients with older ages, cognitive dysfunction and ICD, some studies suggest that DA agonists should be avoided and only levodopa is recommended; while other recent studies published found DA agonists such as Rotigotine are safe in these patients, and they can bring greater motor and non-motor benefits at the same time [ 72 , 75 ].…”
Section: Sleep Disorders and Pharmacological Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 17 ] Pramipexole is a nonergot dopamine agonist with a high binding specificity for the dopamine D 3 receptor subtype that is effective in the treatment of motor symptoms of PD. [ 18 19 ] Dopaminergic pathway dysfunction has been shown a role in the pathogenesis of depression. [ 20 ]…”
Section: Introductionmentioning
confidence: 99%
“…The picture related to the nervous system does not improve immediately after lithium is discontinued. Central nervous system symptoms include a state of confusion, encephalopathy, act at the D3 subgroup level, where lithium may have no influence, and may be able to restore the balance in dopamine neurotransmission or the balance between dopamine and acetylcholine [10].…”
Section: Introductionmentioning
confidence: 99%